Results of the Study of Using the Experimental Sample of the Deep Ripper Tool on Overconsolidated Soil - Galina G. Parkhomenko; Igor V. Bozhko; Sergey I. Kambulov; Nikita V. Buzhinsky (Инженерные технологии и системы, 2025)
Introduction. Under modern conditions, a serious problem for science and technology is increasing anthropogenic loads on the soil caused by agricultural machinery that leads to the soil consolidation. Soil overconsolidation occurs when there is a lack of organic matter and moisture. In the zone of insufficient moisture, the humus mineralization processes prevail over its formation process, so overconsolidation leads to an increase in the soil volume weight (soil density). One way to solve this problem is to use boardless deep rippers. Aim of the Study. The aim of the study is to synthesize element and aggregate components of the deep ripper tool for high-quality soil cultivation. Materials and Methods. Identifying the indicators of the technological process of the experimental sample of the tool for deep soil cultivation was carried out using standard and original methods of studying the soil breaking up quality indicators. Results. The study has shown that with rods in the design of the tool, in terms of lumpiness, the lumps are concentrated mainly in the upper layer of the tilled layer (0...10 cm), and if there are no rods in the tool – in the lower layers (20...30 and 30–40 cm). Soil porosity as a function of density does not reach optimal values (over 50%) in the lower soil layers (37 and 32...33% at 20...30 cm; 31 and 34...35% at 30...40 cm for the backgrounds of disked stubble of cereals and autumn fallow, respectively). Discussion and Conclusions. As a result of the study, it has been found realistic to equip the deep ripper tool with curved rods. It has been determined that the sweeps in the design of the tool must be installed not at a right angle to the rack in the transverse direction, but at an angle of soil chipping therefore land clearer is transformed into a chisel with gap expanders to improve the quality of cultivation and reduce energy costs. Improving the design of a deep ripper tool is also possible by increasing the angle of installation of the sweep to the furrow pan.